EFFECTS OF VAGINAL DOUCHING TO CERVICITISIN OBSTETRICITIONS CLINICS R SOSODORO DJATIKOESOEMO BOJONEGORO 2016 - Azizah, Nur; Luthfia, Erien (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2017)
Vaginal douching is defined as an effort to purge the vagina both external and internal. Vaginal douching is one of the factors causing cervicitis, in Obstetricitions clinics RSUD ClassB Dr R Sosodoro Djatikoesoemo Bojonegoro. cervicitis is a case of infection is most common (53%) compared with other genetalia infection is vaginitis and adneksitis, besides cases of cervicitis was also an increase of 4% in 2010 compared to last year. Therefore, this study investigated the effect of the use of vaginal douching with cervicitis incidence in Obstetricitions clinics RSUD ClassB dr R Sosodoro Djatikoesoemo Bojonegoro. Objective of research is to know the association on the use of vaginal douching with cervicitis incidence in Obstetricitions clinics RSUD Kelas B dr R Sosodoro Djatikoesoemo Bojonegoro.Methode research is observational analytic study used a cross secsional research design. Data taken with the guided interview to the independent variable (the use of vaginal douching) and uses a patient's status for the dependent variable (incidence of cervicitis) in 38 responden.sampel taken by purposive sampling technique to include multiple criteria for inclusion. Having done the research and data analysis using SPSS 17 with significance (? = 0.05)Result of study found the P value 0.021 association use vaginal douching with cervicitis in Obstetricitions clinics RSUD ClassB dr R sosodoro Djatikoesoemo Bojonegoro but the association is low.Suggestedhealth carefacilitiesshouldenhance the roleandhealth education for women to increase personal and vaginal hygiens and then do not make vaginal douching.